CaMKIIβ Association with the Actin Cytoskeleton Is Regulated by Alternative Splicing - O'Leary, Heather; Lasda, Erika; Bayer, K. Ulrich (Molecular biology of the cell, 2006)
The Ca 2+ /calmodulin (CaM)-dependent protein kinase II (CaMKII)β has morphogenic functions in neurons not shared by the α isoform. CaMKIIβ contains three exons (v1, v3, and v4) not present in the CaMKIIα gene, and two of these exons (v1 and v4) are subject to differential alternative splicing. We show here that CaMKIIβ, but not α, mediated bundling of F-actin filaments in vitro. Most importantly, inclusion of exon v1 was required for CaMKIIβ association with the F-actin cytoskeleton within cells. CaMKIIβe, which is the dominant variant around birth and lacks exon v1 sequences, failed to associate with F-actin. By contrast, CaMKIIβ′, which instead lacks exon v4, associated with F-actin as full-length CaMKIIβ. Previous studies with CaMKIIβ mutants have indicated a role of nonstimulated kinase activity in enhancing dendritic arborization. Here, we show that F-actin–targeted CaMKIIβ, but not α, was able to phosphorylate actin in vitro even by nonstimulated basal activity in absence of Ca 2+ /CaM. In rat pancreatic islets and in skeletal muscle, the actin-associated CaMKIIβ′ and βM were the predominant variants, respectively. Thus, cytoskeletal targeting may mediate functions of CaMKIIβ variants also outside the nervous system.